Different Ultrasound Exposure Times Influence the Physicochemical and Microbial Quality Properties in Probiotic Goat Milk Yogurt - Delgado, Karina (Molecules, 2020)
Despite goat milk having health benefits over cow milk, goat milk yogurt (GY) presents low consistency and viscosity, which reduces its overall acceptability by the consumer. Thus, new innovative methods can be an alternative to improve the quality of GY. Hence, this study aimed to investigate the effect of ultrasound (US) treatment with different sonication times on quality parameters of probiotic GY during refrigerated storage. US treatment was conducted at 20 KHz for 3, 6, and 9 min in yogurt. Lactobacillus bulgaricus and Lactobacillus acidophilus LA-5 were sensitive to US treatment, presenting a decrease in the yogurts stocked. This loss of viability led to reduced post-acidification due to smaller lactose metabolization in yogurt samples submitted to the US. Among tested treatments, the application of 6 min enhanced the apparent viscosity and consistency index of GY yogurts. In addition, this time also reduced tyramine and total biogenic amine (BAs) content. These findings suggest that 6 min of sonication is a promising way to improve the rheological properties and reduce the acidity and BAs content in GY. Further studies should be performed to optimize the US setting conditions to preserve the probiotic culture viability in yogurts.